Identification of female specific protein in seabass, Lates calcarifer (Bloch) - Lal, Kuldeep Kumar; Gopalakrishnan, A; Mohindra, Vindhya; James, P S B R (Indian Journal of Fisheries, 2011)
Electrophoretic serum protein profile of female Lates calcarifer reveals appearance of female specific protein during gonadotropic dependent stages of ovarian growth. The protein is conspicuously absent in the serum of maturing males. The protein stains positively for carbohydrate, lipids and calcium indicating it to be vitellogenin. The vitellogenin band first appears in fish with maturing ovaries (stage 3) and stain intense and sharp till stage 4. At stage 5 (ripe) the band appears diffused. The protein is lacking in the serum profile of immature (stage 1), restingpreparatory (stage 2) and spent (stage 6) as well as in maturing male fish. The correlative pattern of vitellogenin band with ovarian maturation stages provides evidence of single spawning in L. calcarifer.